Method total physical response para desarrollar el listening and speaking en los niños de 10 a 11 años de la parroquia San Sebastián, cantón Chimbo, provincia Bolívar en el periodo 2016. - Oñate Montes, Dolores Fernanda (2016)
The present work of research is oriented to the search of active forms of teaching-learning of the English language, from this perspective this work has been organized starting from the selection of the topic which has been synthesized as follows: Total Physical Response Method for To develop the listening and speaking in the children of 10 to 11 years in San Sebastián, Chimbo canton, province Bolivar in the period 2016. On the other, hand in the canton Chimbo, Bolívar province, especially in the parroquia San Sebastián the English according to statistical data it was verify the problem in the language learning persists. In many South American countries, learning English has not been successful in recent years. This fact has become known after some investigations carried out by specialists in linguistic subjects. Many of the errors of English teaching have allowed the generations of students to not be able to handle a second language, another aspect that is important to emphasize that educational institutions have to do with the erroneous attempt to memorize what has been learned, but not internalize it and reflect About the importance of learning English. English is indisputably the "lingua franca" of the world today, not only because all technological, scientific, academic, and social information updates are written in English, but also to learn to speak more of a foreign language as it is Essential to master the English in order to interact and communicate with the globalized world of today, therefore, the current education has the challenge of contributing to the development of skills and skills in it. Total Physical Response (RFT) is a method of language teaching that combines speech with action and proposes to teach the language through physical activity. J. Asher, professor of psychology at San Jose State University, California, develops a method the method relates to the theory of memory in psychology. Asher mentions that the connection to memory may be stronger if it is established through verbal repetition or through association with a motor activity. This method makes use of the commands technique, the following instructions. Grammar is taught in an inductive way since the method requires that at first attention be centered on the meaning. The TPR is a teaching method that includes the knowledge and five senses of the learner. The children put on the stage or move according to what the teacher says at that time, for it is used games with movement, commands, theatrical scenes and songs such as "If you're happy and you know it, clap your Hands ... "(" If you are happy and you know how to applaud "), learners live and understand languages intensely and globally. With this method, the children have been motivated to learn the language. We have used dynamics, commands, audio-videos, play games, flashcards and so on. Which have been favorable to raise the level of learning, we can finally say that we have met our objectives